Transformation of Business Models in the Industry 4.0 and Digital Economy - Gaiterova, O.; Kapustina, L.; Kondratenko, J. (KU Publ., 2020)
Digitalization forms a new type of economy. Over the past few decades, international corporations have faced various challenges: technological changes, increasing complexity of production, changing consumer preferences,etc. This has led to a transformation of business models: an increasing number of companies are using digital technologies in their operations.In the article, the authors study the stages of business models transformation and identify criteria for classifying "smart enterprises". The authors analyzed the process of digitalization in international corporations, identified their characteristics, developed a classification of enterprises in Industry 4.0 and digital economy, and provided examples for each type.
Keywords: business model; digital economy; industry 4.0; digitalization; smart enterprise